Digital Learning Media Assisted by Quizizz Application (METALIQ) on Science Content of Ecosystem Topic for Sixth Grade Elementary School - Nanda Sekar Astafiria; Gede Wira Bayu (Jurnal Ilmiah Sekolah Dasar, 2021)
This study aims to produce â€œMETALIQâ€ which was developed on the topic of Ecosystems for the sixth-grade elementary school students. This research was a development research based on the ADDIE model procedure. The subject of this research was "METALIQ" with the topic Ecosystem for sixth grade elementary school students involving four lecturers as experts who assess the validity of the product content, two teachers who provide practitioner responses, and 10 sixth grade elementary school students filling out student responses. The object of research was the feasibility of "METALIQ" which is viewed from the content validity, practitioner responses, and student responses. The data collection methods in this study were observation, interviews, document studies, questionnaires and instruments rating scale. To measure the validity of the content of "METALIQ", the instrument was used rating scale, meanwhile to measure the responses of practitioners and studentsâ€™ responses used a questionnaire. The learning media validity data obtained were then analyzed using the Aikenâ€™s V formula to measure the content validity coefficient. The mean is an analysis to determine the average score of teacher responses and student responses. The results of the analysis of the validity of the â€œMETALIQâ€ data for content experts were in the range of 0.75-1.00 and learning media experts were in the range of 0.625-1.00. This indicated that the content validity of â€œMETALIQâ€ was high. The practitioner response test got an average score of 4.3, and the student response test got an average score of 4.55. This means that all aspects of the response test to â€œMETALIQâ€ have very good qualifications. Based on this analysis, â€œMETALIQâ€ in the science content of the Ecosystem topic was feasible for use in learning.